1960
DOI: 10.5254/1.3542164
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance of Radicals Formed during Milling

Abstract: It is well known that during the mechanical degradation of polymers there takes place scission of molecular chains and the formation of macroradicals. It is of considerable interest to study the electron paramagnetic resonance (EPR) spectra of the macroradicals produced by milling, and to compare them with the spectra of the macroradicals formed in the process of polymerization, and also during the irradiation of polymers by gamma rays and neutrons. We may endeavor to compare the amount of macroradicals formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ESR spectroscopy was successfully applied for study of free radicals generated during fracture in rubber45, 46,306,307,320,321,371,536,537,546,1100,1453,1578,1765,1822,1839,1878,2400) and especially in ozone atmosphere 537,539,544,545,548). The results obtained were reviewed in detail by DeVries 537 ).…”
Section: Esr Study Of Free Radicals Formed During Fracture In Rubbermentioning
confidence: 99%
“…ESR spectroscopy was successfully applied for study of free radicals generated during fracture in rubber45, 46,306,307,320,321,371,536,537,546,1100,1453,1578,1765,1822,1839,1878,2400) and especially in ozone atmosphere 537,539,544,545,548). The results obtained were reviewed in detail by DeVries 537 ).…”
Section: Esr Study Of Free Radicals Formed During Fracture In Rubbermentioning
confidence: 99%
“…They showed that most polymers, particularly in plasticized form, undergo a rapid reduction in molecular weight on cold mastication and that the macroradicals produced by shear initiate conventional free radical processes. In the presence of air the macroradicals are converted rapidly to alkylperoxy radicals (3,8). The change in applied torque with time during the processing of PVC in a typical mixer (RAPRA torque rheometer) at two temperatures is shown in Figure 1.…”
Section: Mechanooxidation Of Polymers During Processingmentioning
confidence: 99%